Identification of Micro-plastics (MPs) in Conventional Tap Water Sourced from Thailand - Dinuka Kankanige; Sandhya Babel (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
In a period when MP contamination of drinking water is a great concern, this study focused on the size- and morphology-based count, and polymeric identification of plastic particles in tap water sourced from Thailand. A total of 45 human consumable samples (each 1 L) were collected at Thammasat University. The average MP counts sorted by Nile Red tagging were 56.0±14.0 p/L (6.5-53 µm) and 21.0±7.0 p/L (53-300 µm), while those found by optical microscopic observations were 13.0±5.0 p/L (300-500 µm) and 6.0±3.0 p/L (â‰¥ 500 µm). A significantly high MP amount was observed in the 6.5-53 µm fraction. Fibers dominated in all samples, accounting for 58% of the particle count. Most â‰¥ 300 µm particles tested by ATR-FT-IR spectroscopy were confirmed to be polymeric, identified as PE, PVC, PET, PA, PTFE, PP, and PAM. These particles may have escaped from the treatment plant or were added along the water distribution network. Since MPs in drinking water constitute a potential health risk by exposing humans to direct plastics intake, MP contamination in water supply systems should be controlled.